Optimasi Penurunan Kandungan Oligosakarida pada Pembuatan Tepung Ubijalar dengan Cara Fermentasi - Sukardi, Sukardi; P., M. Hindun; Hidayat, Nur (Jurnal Teknologi Pertanian, 2001)
The aim of the experiment is to determine the optimal level of fermentation to decreasing oligosaccharide of flour from Ipomoea batatas. The experiment is carried out in Factorial Randomized Block Design.  First factor is time of blanching, i.e. 5, 10 and 15 minutes, and the second factors is time of fermentation, i.e. 12, 24 and 36 hours respectively.  Parameters observed include fiber content, water content and sensory characteristics as like color and aroma of flour. The result show that an time of blanching 5 minutes and time of fermentation 12 hours is found to be optimum one to produce good quality flour.  It will be reducing total oligosaccharide from 2.165 % to 0.307 %.  The flour contains 5.12 % fiber, 5.29 % water and it is still considered to be acceptable in terms of color and aroma.   Keywords: Ipomoea batatas, fermentation, oligosaccharide